2003
DOI: 10.1046/j.1365-2427.2003.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproduction of three cladoceran species from a small wetland in the south‐eastern U.S.A.

Abstract: SUMMARY 1. Growth, reproduction and life‐history parameters were measured for three cladoceran species from a small south‐eastern wetland, U.S.A. Simocephalus serrulatus, Diaphanosoma brachyurum and Scapholeberis mucronata juveniles were reared at temperatures between 10 and 25 °C on natural food resources. 2. Growth rate increased with temperature and decreased with individual size for all three species. Maximum somatic growth rate was higher for Simocephalus (49–72% day−1) and Diaphanosoma (21–91% day−1) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
4
25
0
6
Order By: Relevance
“…Diaphanosoma generally reached a peak density in about 2 weeks (Lemke and Benke, 2003;Han et al, 2011), a trend also observed in the present study. When raised exclusively on H. pluvialis, D. birgei showed a lower growth than if they were cultured on mixed food which actually improved growth rates.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Diaphanosoma generally reached a peak density in about 2 weeks (Lemke and Benke, 2003;Han et al, 2011), a trend also observed in the present study. When raised exclusively on H. pluvialis, D. birgei showed a lower growth than if they were cultured on mixed food which actually improved growth rates.…”
Section: Discussionsupporting
confidence: 91%
“…Diaphanosoma brachyurum had an r rate of 0.32 ind. day -1 at 25°C (Lemke and Benke, 2003); D. dubium had an r rate of 0.29 ind.day -1 at 29°C (Han et al, 2011) and the r rates of D. birgei in the current study were similar among the three diets (Ag; at temperature 24°C. In fact, they agreed with published ranges of other cladocerans species reared at similar temperatures and with various food conditions (Lemke and Benke, 2003;Ismail et al, 2011).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations